Analisis Normatif Peran Aparat Penegak Hukum Dalam Menanggulangi Penyelundupan Narkotika Terhadap Aparat Penegak Hukum Yang Terlibat - Rufaidah; Sarah Alzagladi; Hasan Alzagladi; Fitri Ramadhani; Ahmad Sayadi (Consensus : Jurnal Ilmu Hukum, 2026)
This study aims to conduct a normative analysis of the role of law enforcement officials in combating drug smuggling, with a specific focus on the involvement of corrupt officials in such crimes. This issue is critical because the involvement of law enforcement officials not only undermines the integrity of law enforcement institutions but also has the potential to weaken the effectiveness of comprehensive narcotics eradication efforts. This study examines the legal framework regarding the roles, authorities, and responsibilities of law enforcement officials within the criminal justice system, and evaluates its alignment with actual practices on the ground. Additionally, the study analyzes the forms of criminal liability and the sanctions imposed on officials involved in drug smuggling. The method used is normative legal research employing a statutory approach and a conceptual approach. Legal sources include primary legal materials in the form of laws and regulations related to narcotics and law enforcement, secondary legal materials such as books, journals, and legal doctrines, as well as tertiary legal materials for supplementary purposes. Legal materials were collected through a literature review, which was then qualitatively analyzed to produce systematic conclusions. The results of this study are expected to contribute to strengthening law enforcement and enhancing the integrity of law enforcement officials in efforts to eradicate narcotics smuggling.